Stimulation of hyphal growth in anaerobic cultures of Mucor rouxii by extracellular trehalose. Relevance of cell wall-bound activity of acid trehalase for trehalose utilization - Lucio, A.K.B; Lourdes, M. de; Polizeli, T.M; Jorge, J.A; Terenzi, H.F (FEMS microbiology letters, 2000)
In fungi, the hydrolysis of extracellular trehalose is carried out by acid trehalases. These secretory glycoproteins may be more abundant either in the vacuolar compartment, like in yeast, or at the cell surface, such as in many filamentous fungi. The relative efficiency of these two compartments for the utilization of extracellular trehalose was investigated using as a model the dimorphic fungus Mucor rouxii, which produces yeast-like cells under a CO2 atmosphere, or hyphae in the presence of air. Under CO2, cultures supplemented with glucose produced yeast-like cells devoid of acid trehalase activity. On the other hand, trehalose-supplemented cultures developed hyphae exhibiting cell wall-bound and intracellular acid trehalase activity. Glucose-grown yeast-like cells supplemented with trehalose after glucose exhaustion, induced intracellular activity of acid trehalase, but no activity was detected at the cell surface. Even endowed of significant intracellular activity of acid trehalase, these cells did not grow further. When exposed to air these yeast-like produced germ tubes exhibiting cell wall-bound acid trehalase activity. These results suggest that the utilization of extracellular trehalose as a source of carbon for growth requires the localization of acid trehalase activity at the cell surface. Our results also show that extracellular trehalose elicits a morphogenetic phenomenon, inducing the formation of hyphae which are the physiological support for acid trehalase activity.